The Role of University-Industry Linkage in Creating a Functional Technical and Vocational Education and Training (TVET) in Nigeria - Nnaemeka M. Agbo; Francisca N. Nnajiofor (Journal of Vocational Education Studies, 2023)
This study was on the role of university-industry linkage in creating a functional technical and vocational education and training (TVET) in Nigeria. The study specifically looked into the concept of TVET, types of university-industry linkage, reasons for university-industry linkage, current status of university-industry linkage, challenges mitigating university-industry linkage, strategies for effective university-industry linkage in the universities and the role of viable university-industry linkage in creating a functional technical and vocational education and training. It was noted that in order to build a viable linkage between the universities and the industries, legislators at both federal and state levels need to come up with laws and policies that will foster university-industry linkage with clear implementation strategies, compulsory periodic internship for both lecturers and students, integration of professionals from the industries in the TVET curricula planning and implementation processes. It was concluded that when a strong linkage is established between the universities and industries, TVET will receive the dividends and as such be made functional and effective.